Carotid-Cavernous Fistula in the Emergency Department - Gurger, Mehtap; Ekingen, Evren; Atescelik, Metin; Alatas, Omer Dogan; Yildiz, Mustafa (Aves, 2014)
Introduction: A carotid-cavernous fistula results from abnormal communication between the internal or external carotid arteries and the cavernous sinus. It occurs because of traumatic or spontaneous rents. Seventy-five percent of the cases are traumatic. The etiology of spontaneous fistula is unknown but is thought to occur as a result of rupture of an arteriovenous malformation. Spontaneous fistula usually occurs in middle-aged or elderly women. Atherosclerosis, systemic hypertension, collagen vascular disease, pregnancy, connective tissue disease, and minor trauma may be predisposing factors in the development of spontaneous carotid-cavernous fistula. The clinical presentations of patients are pulsating or nonpulsatile exophthalmus, chemosis, reduced eye movements, blurred vision, seconder glaucoma, murmur, tinnitus, and headache. Case Report: In this report, a 45-year-old female patient with a spontaneous carotid-cavernous fistula that developed after severe headache, nausea, and vomiting is presented. Conclusion: Carotid-cavernous fistula is a disease that is rarely seen and difficult to diagnosis and needs to be considered in the emergency department; it can be treated profoundly with early diagnosis and treatment.
Keywords: Carotid-cavernous fistula; emergency department